Application The Optimal Value Of Ordering Rattan Craft Raw Materials - Hendra Pribadi; Syukur Umar; Abdul Rahman; Hamka Hamka (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Weaving is a hereditary culture passed down by people in Indonesia and various types of its crafts produce higher economic value. Therefore, this study aims to measure whether the rattan craftsmen have achieved optimal orders and products by calculating the period of the order quantity (POQ) and Economic Production Amount (EPQ) for six months. The average value of ordering raw materials from actual data and analysis results was 918 kg. The results also showed that the production needs to be increased by 40%, but after this analysis was applied to the craftsmen, they cannot increase revenues. However, they can reduce costs in ordering raw materials. This indicates that the solution from this study cannot be applied optimally because the craftsmen do not want to take the risk of making more products but only based on orders.